Professor Mikołaj ŁABOWSKI - Hornowski, Tomasz (Archives of Acoustics, 2013)
Mikołaj Łabowski, Professor Emeritus at the Institute of Acoustics, Adam Mickiewicz University in Poznań, passed away on the 18th of October, 2013